Ruang Khusus Dalam Perancangan Arsitektur Studi Kasus Perancangan CSSD (Central Sterile Supply Department) - Dwiasta R, Andi Yusdy; Asnur, Moeh. Kay Muddin (Jurnal Pendidikan Teknik Sipil dan Arsitektur, 2023)
Studies in the architectural design space will make the design work more optimal design and targeted, one way is to pay attention to aspects of the design. Physical aspects and non-physical aspects of becoming an effort to manipulate the architectural space in order to avoid improper assumptions in architectural design.